Association Between Vitamin D Status and Schizophrenia: A First Psychotic Episode Study. Issue 5 (May 2017) - Salavert, José; Grados, Dolors; Ramiro, Nuria; Carrión, Maria Isabel; Fadeuilhe, Christian; Palma, Felipe; López, Laura; Erra, Alba; Ramírez, Nicolás
Abstract : Abstract: Vitamin D deficiency has been linked with schizophrenia. We aimed to determine whether patients with a first episode of psychosis (FEP) had lower vitamin D levels compared with controls considering their final diagnosis. We conducted a cross-sectional study determining 25-hydroxyvitamin D blood levels. 25-Hydroxyvitamin D levels were considered optimum at 20 ng/mL or greater. A group of 45 adult patients with FEP and a group of 22 healthy controls matched for age were recruited. The patient group was subdivided in two final diagnosis groups (schizophrenia versus other psychoses) after a 6-month follow-up. Average vitamin D values were deficient for FEP patients, especially those 22 with a final diagnosis of schizophrenia. These results relating vitamin D and schizophrenia generate interest to further examine this association.